Affirming students' right to their own language [ bridging language policies and pedagogical practices - Katz, Laurie; Scott, Jerrie Cobb; Straker, Dolores Y. [ (Dolores Yvonne] , 1947-2008 (Routledge;Urbana, Ill : National Council of Teachers of English, 2009)
Chronicling the interplay between legislated/litigated education policies and language and literacy teaching in diverse classrooms, this book presents research-based practices that maximize students' learning by utilizing their home-based cultural, language, and literacy practices to help them meet school expectations.